Research on the DC Ice-Melting Model and Its Influencing Factors on the Overhead Contact Systems of an Electrification Railway - Guosheng Huang; Mingli Wu; Jieyi Liang; Songping Fu; Fuqiang Tian; Xiaojuan Pei; Qiujiang Liu; Teng Li (Energies)
The overhead contact system of the electrification railway is exposed to the natural environment throughout the year and is liable to encounter the problem of line icing. The icing on the line will reduce the current-collection performance of the pantograph, resulting in a decrease in the safety and reliability of the overhead contact system. It is an effective way to solve the icing problem by using the Joule heat generated by the DC in the conductor to melt the ice. In this paper, the multi-physics simulation software COMSOL is used to construct the finite element simulation model of the overhead contact system unit composed of a contact line, catenary wire and dropper. The model covers the physical processes such as convective heat transfer between conductor and air, heat conduction between overhead contact system and ice layer during ice melting, and considers the latent heat factor of ice melting. Under the condition of no icing, the actual data of several temperature points are measured under the applied current state of the overhead contact system, and the validity of the model is verified by comparing the simulated temperature data with the measured data. On this basis, the effects of ambient temperature, ice thickness and current on ice melting were studied using simulations. The results show that the ambient temperature has a significant effect on the ice-melting speed. Under 10 mm ice thickness and 2 m/s wind speed conditions, the time to start melting ice increases from 2 to 60 min until the ice cannot be melted as the ambient temperature decreases from −1 °C to −25 °C. Various initial conditions for ice thickness and wind speed were analyzed. Under the condition of no ice, the temperature rise of the contact wire and the catenary wire increases significantly with the current increase. When the current increases from 500 A to 2000 A, the temperature rise of the contact wire increases from 9.08–9.25 °C to 214.07–218.59 °C, and the temperature rise of the catenary wire increases from 6.88–7.01 °C to 173.43–177.13 °C. In addition, there is an optimal ice thickness range for the ice-melting process. When melting ice at −1 °C and −5 °C, the optimal ice thickness ranges are 4–8 mm and 1–4 mm, respectively.